Penanaman kesadaran pemilahan sampah organik dan anorganik melalui metode PAR di Desa Pengasinan, Kota Depok - Najwatu Sholihah; Siti; Afifah; Muhamad; Ajat; Yudril (Universitas Sanata Dharma, 2026)
The problem of household waste management in Indonesia, particularly in Pengasinan subdistrict, Depok City, is still characterized by low public awareness in sorting organic and inorganic waste and a lack of supporting facilities. This community service research aims to instill public awareness in waste sorting through a participatory approach. The method used is Participatory Action Research (PAR) with the stages of observation, reflection, action planning, socialization-education actions, and evaluation for one month in 33 residents of RT 007/RW 010. The results showed that before the intervention, most residents mixed waste, threw it into the gutter, or burned waste due to limited knowledge and facilities. After socialization with the village and DLHK (Environment and Sanitation Agency), there was an increase in understanding and behavioral changes, especially among housewives who began to sort waste at the household level. However, the sustainability of the practice is still hampered by the lack of infrastructure, such as segregated waste bins and waste banks. It was concluded that the PAR method is effective in increasing public awareness and practice of waste sorting, but the sustainability of behavioral changes is highly dependent on the support of local government facilities and policies.